İndüksiyon ısıtma ile mikro ve nano desenlerin polimer yüzeylere baskılanması - Demirci, Havva (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2022)
Bu çalışmada belirli polimerlerin yüzeylerinde mikro ve nano desenlerin oluşturulma yöntemleri incelenmiştir. Birinci aşamada mevcut litografik yöntemlerin aksine daha az maliyetli ve daha az ekipman gerektiren sıcak baskılama cihazı tasarlanmıştır. Tasarım yapılırken en kısa sürede en iyi transferin sağlanabilmesi için en uygun malzeme seçimi ve çalışma prensibi belirlenmiştir. İkinci aşamada üretimi sağlanmış olan sıcak baskılama cihazı ile işlem parametrelerinin (sıcaklık, basınç, süre) optimizasyon çalışmaları yapılmıştır. Belirlenen çalışma koşullarında nikel kalıp yardımıyla alternatif manyetik alan oluşturulup indüksiyon ısıtma yaparak polimer yüzeyine mikro ve nano desen transferi gerçekleştirilmiştir.

In this study, the methods of forming micro and nano patterns on the surfaces of certain polymers were investigated. In the first step, a hot imprinting device was designed which is less costly and requires less equipment, unlike the existing lithographic methods. While designing, the most suitable material selection and working principle were determined in order to ensure the best transfer in the shortest time. Optimization studies of the process parameters (temperature, pressure, time) were carried out with the hot imprinting device which was produced in the second step. In the determined working conditions, an alternative magnetic field had been created with the help of a nickel mold and micro and nano pattern transfered to the polymer surface is carried out by induction heating.
Imprinting micro and nano patterns on polymer surfaces with induction heating
Keywords: Kimya Mühendisliği; Chemical Engineering